1999
DOI: 10.1097/00005344-199908000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP Protein Kinase Mediates Negative Metabolic and Functional Effects of Cyclic GMP in Control and Hypertrophied Rabbit Cardiac Myocytes

Abstract: We tested the hypothesis that in isolated cardiac myocytes, the negative metabolic and functional effects of cyclic guanosine monophosphate (GMP) are mediated by cyclic GMP protein kinase activity, and that these effects are altered in renal hypertensive (one-kidney, one-clip, 1K1C) cardiac hypertrophic rabbits. By using isolated cardiac myocytes from control and 1K1C rabbits, oxygen consumption (Mvo2; O2 nl/ min/10(5) cells), cyclic GMP (fmol/10(5) cells), and cell shortening (percentage) data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…Several studies from our laboratory have shown that cyclic GMP has negative metabolic and functional effects on isolated cardiac myocytes [7,19,20]. These findings were similar to the reports of others [1,2,23,25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies from our laboratory have shown that cyclic GMP has negative metabolic and functional effects on isolated cardiac myocytes [7,19,20]. These findings were similar to the reports of others [1,2,23,25].…”
Section: Discussionsupporting
confidence: 89%
“…The cyclic GMP phosphodiesterase that hydrolyzes cyclic GMP can be inhibited by the specific cyclic GMP phosphodiesterase inhibitor zaprinast. Two previous studies from our laboratory demonstrated that zaprinast decreased intracellular cyclic GMP levels [19,20]. It is not clear over what range changes in cyclic GMP negatively correlate with cardiac myocyte function.…”
Section: Introductionmentioning
confidence: 85%
“…This concentration of zaprinast has been shown to significantly amplify the effects of atrial natriuretic factor and to increase intracellular cGMP levels in rabbit ventricular myocytes. 12,13 In muscle strip preparations, zaprinast significantly reduced isometric tension development (data not shown). cGMP-dependent protein kinase (PKG-I) was inhibited with KT-5823 (Sigma) dissolved in ethanol (final concentration, 0.01%) and added to the medium at 1 mol/L, a concentration previously shown to suppress PKG-I-mediated effects of PDE-5 inhibition and exogenous nitric oxide in rabbit ventricular myocytes.…”
Section: Pharmacological Interventionsmentioning
confidence: 86%
“…cGMP-dependent protein kinase (PKG-I) was inhibited with KT-5823 (Sigma) dissolved in ethanol (final concentration, 0.01%) and added to the medium at 1 mol/L, a concentration previously shown to suppress PKG-I-mediated effects of PDE-5 inhibition and exogenous nitric oxide in rabbit ventricular myocytes. 13,14 All agents were present from the onset of the 60-minute equilibration period and throughout the entire incubation period. Appropriate vehicle control groups were included for every investigated combination of agent and loading condition.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Previous work has shown that the second messenger cyclic GMP reduces myocardial metabolism, inotropy and function [1][2][3][4]. The negative functional effect of cyclic GMP in cardiac myocytes is mediated through cyclic GMP-gated ion channels, cyclic GMP-regulated phosphodiesterases and cyclic GMP-dependent protein kinases [5][6][7].…”
Section: Introductionmentioning
confidence: 99%